Perceived Boundarylessness in Relation to Success Factors: A Descriptive Study of Nine Bangalore Organizations in the IT Sector - Mathew, Mary; Pushpa, Randhir Reghunath (UI Scholars Hub, 2008)
The importance of organization boundaries and their nature of permeability is of special concern in a globalized world. The role of systems theorists and that of boudary management intervention theorists show the need to study the people sub system more. Managerial perceptions are critical in this context. Sensing and perceiving boundarylessness will lead to a better consciousness of boundary management. This paper describes the way nine HR managers perceive their boundaries in the IT sector of Bangalore. The managers are asked about various types of boundaries namely, vertical, horizontal, external, geographic, and psychological boundaries. The boundaries are also understood in terms of success factors namely, innovation, flexibility, speed, and integration. Results show variations in managerial perception of organizational boundarylessness in the context of the boundary types. Interestingly innovation remains controversial as none of the Indian managers concur on the influence of boundaries on innovation.